2020
DOI: 10.1007/s00262-020-02650-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing caspase-1 involvement during esophageal disease progression

Abstract: Barrett's esophagus (BE) is an inflammatory condition and a neoplastic precursor to esophageal adenocarcinoma (EAC). Inflammasome signaling, which contributes to acute and chronic inflammation, results in caspase-1 activation leading to the secretion of IL-1β and IL-18, and inflammatory cell death (pyroptosis). This study aimed to characterize caspase-1 expression, and its functional importance, during disease progression to BE and EAC.Three models of disease progression (Normal-BE-EAC) were employed to profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Barrett's esophagus (BE) can also activate caspase-1-dependent pyroptosis and cause the release of IL-1β and IL-18 to enhance the progression of esophageal cancer. 33 Additionally, Gao et al 34 formation. NLRP3 can stimulate pyroptosis and the release mature IL-1β or IL-18 to decelerate host immunity in gastric tumorigenesis.…”
Section: Inflammasome-mediated Pyroptosis Promotes Tumor Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Barrett's esophagus (BE) can also activate caspase-1-dependent pyroptosis and cause the release of IL-1β and IL-18 to enhance the progression of esophageal cancer. 33 Additionally, Gao et al 34 formation. NLRP3 can stimulate pyroptosis and the release mature IL-1β or IL-18 to decelerate host immunity in gastric tumorigenesis.…”
Section: Inflammasome-mediated Pyroptosis Promotes Tumor Developmentmentioning
confidence: 99%
“…Barrett's esophagus (BE) can also activate caspase‐1‐dependent pyroptosis and cause the release of IL‐1β and IL‐18 to enhance the progression of esophageal cancer. 33 Additionally, Gao et al 34 described a novel mechanism by which GSDMD‐mediated pyroptosis may aid non‐small‐cell lung cancer (NSCLC) to evade the innate immune response through the dysregulation of immunomodulatory factors, such as IL‐1β. The report published by Pachathundikandi et al reiterated that Helicobacter pylori , which always colonizes in the stomach, could promote NLRP3 inflammasome formation.…”
Section: The Role Of Pyroptosis In the Association Between Cancer And The Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue from the cardia region at the squamous-columnar junction (SCJ) of 12-month old L2-IL-1B mice was processed for 3D organoid culture in Matrigel for 3 weeks, as previously described [ 20 , 21 ]. Three days before harvesting, organoids were pre-treated (1 h) with the αTLR2 neutralising antibody (10 μg/mL) followed by 24 h stimulation with P2C (40 ng/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Caspase-1 mediates the inflammatory disease BE, which can further develop into EAC. Barber et al showed that the secretion of inflammatory cytokines and chemokines is reduced in BE patient biopsies and in mouse BE organ cultures in vitro via inhibition of caspase-1 [ 81 ]. The expression of caspase-activated GSDMD is beneficial for inhibiting the proliferation of gastric cancer cells.…”
Section: Introduction To Programmed Cell Death and Pyroptosismentioning
confidence: 99%